Educação para a não violência : uma leitura à luz da filosofia de Eric Weil - Carneira, Marcelo Larger (My University, 2024)
This Thesis aims to demonstrate that education for nonviolence, from the perspective of Eric Weil, has a sense of Aristotelian practical wisdom. To explore this theme, we started from the following question: What is the meaning of education for Eric Weil in the formation of people capable of perceiving their place in the world and of the other, subsidizing an openness to the promotion of progress towards nonviolence? For Weil, education has a special place in his interpretation of how mankind acts in historical reality, starting from a concept of moral education. For him, education is not limited to instruction, but aims to provide the individual with a development of the ability to understand his place in the world and his relationships with other individuals. The hypothesis raised is that education has similar contours to Aristotelian practical wisdom, because it enables reasonable individuals to develop a deeper understanding of relationships with other members of a community, so that they can act ethically and responsibly. The theoretical basis of this Thesis are Weil's books, especially the Logic of Philosophy, Moral Philosophy and Political Philosophy, compared with Aristotle's Nicomachean Ethics, especially with regard to practical wisdom. This research contributes to foster the discussion about the meaning of education in the construction of a society that promotes the formation of individuals who are respectful of others and committed to the promotion of progress towards nonviolence. In addition, it contributes to an understanding of human dynamics, and the ability to adapt to diverse situations, which is fundamental for the evolution of humanity, because it not only provides knowledge, but also shapes attitudes, values, and behaviors that are essential for building a fairer society. [resumo fornecido pelo autor]
Esta Tese tem como objetivo demonstrar que a educação para a não violência, sob a ótica de Eric Weil, tem um sentido de sabedoria prática aristotélica. Para explorar esse tema, partiu-se da seguinte questão: Qual o sentido da educação para Eric Weil na formação de pessoas capazes de perceber seu lugar no mundo e do outro, subsidiando uma abertura para a promoção de um progresso para a não violência? Para Weil, a educação tem um lugar especial em sua interpretação de como o homem age na realidade histórica, partindo de um conceito de educação moral. Para ele, a educação não se resume à instrução, mas visa proporcionar ao indivíduo um desenvolvimento da capacidade de compreender seu lugar no mundo e das suas relações com os outros indivíduos. A hipótese levantada é a de que a educação, da forma como Weil a compreende, tem contornos semelhantes à sabedoria prática aristotélica, porque proporciona aos indivíduos razoáveis desenvolverem uma compreensão mais profunda das relações com outros membros de uma comunidade, de modo que possam agir de maneira ética e responsável. O embasamento teórico desta Tese são as obras de Eric Weil, sobretudo a Lógica da Filosofia, a Filosofia Moral e a Filosofia Política, cotejadas com a obra Ética a Nicômaco, de Aristóteles, especialmente no tocante à sabedoria prática. Esta pesquisa contribui para fomentar a discussão sobre o sentido da educação na construção de uma sociedade que promova a formação de indivíduos respeitosos com os outros e comprometidos com a promoção de um progresso em direção a não violência. Além disso, contribui para uma compreensão das dinâmicas humanas e da capacidade de se adaptar a situações diversas, o que é fundamental para a evolução da humanidade, porque ela não apenas fornece conhecimento, mas também molda atitudes, valores e comportamentos que são essenciais para a construção de uma sociedade mais justa. [resumo fornecido pelo autor]
Keywords: Educação - Filosofia; Filosofia; Weil, Eric, 1904-1977; Sabedoria; Education - Philosophy; Philosophy; Wisdom